Violence and Political Participation in Northeastern Guatemala. (January 2021) - Simon, Saskia
Since colonial times, Northeastern Guatemala has been at the crossroads of legal and illegal trade routes used by local elites and foreign investors. Organized crime has always prospered there with the complicity and participation of the local authorities, while the United Fruit Company started its first banana plantations there in 1904. Both rested their capital accumulation on governmentalities mixing disciplinary and sovereign power mechanisms as analyzed by Foucault. In response to the impact of these governmentalities, centered on control and violence, the population has developed a tactical subjectivity that presents obstacles to its political participation and collective mobilization. Desde la época colonial, el noreste de Guatemala ha estado en la encrucijada de las rutas comerciales legales e ilegales utilizadas por las élites locales y los inversionistas extranjeros. Allí, el crimen organizado siempre ha prosperado con la complicidad y la participación de las autoridades locales, y la United Fruit Company sembró sus primeros platanares en el territorio en 1904. Ambos bandos sustentaron su acumulación de capital en gubernamentalidades que mezclan mecanismos de poder disciplinario y soberano, tal y como los define Foucault. En respuesta al impacto de estas organizaciones gubernamentales, centradas en el control y la violencia, la población ha desarrollado una subjetividad táctica que presenta obstáculos a su participación política y movilización colectiva.